Exploring The Essence of CBT: an Ontological, Epistemological, and Axiological Analysis, and The Contributions of The Thoughts of Aaron T. Beck and Albert Ellis to Guidance and Counseling - Rochiyatin Rifai; Wiryo Nuryono (International Journal Labs, 2026)
This research is motivated by the increasing need for counselling approaches that are not only practically effective, but also grounded in a strong philosophical foundation. Cognitive Behavioural Therapy (CBT), as the dominant approach in modern guidance and counselling practice, needs to be studied in depth through the perspectives of ontology, epistemology, and axiology so that it is not understood merely as an intervention technique. The purpose of this research is to explore the essence of CBT and to identify the contributions of Aaron T. Beck and Albert Ellis to the development of guidance and counselling. This study employs a philosophical qualitative approach using a literature study method that analyses various relevant scientific sources. The results of the study show that ontologically, CBT views humans as rational beings capable of changing their mindset and behaviour through cognitive processes. Epistemologically, CBT is grounded in empirical evidence and systematic scientific validation. Axiologically, CBT is oriented toward adaptive behavioural change and the improvement of individual well-being. Beck's contribution lies in the development of an empirically based cognitive model, while Ellis emphasises rationality and the modification of irrational beliefs. The study concludes that CBT makes a significant theoretical and practical contribution to improving the effectiveness of guidance and counselling services.